Bioactive glass and iron oxide nanoparticle composite coatings for Ti-6Al-4V implants: Microstructure, corrosion behavior, bioactivity and cellular response - Zahra Sohani; Hamed Jamshidi Aval; Sayed Mahmood Rabiee (Applied Surface Science Advances)
The Ti-6Al-4V alloy is widely recognized for its excellent properties, such as biocompatibility, corrosion resistance, and high mechanical strength, making it a popular choice for medical implants. This study focuses on the development of a composite coating consisting of bioactive glass (64SiO₂-31CaO-5P₂O₅ mol%) and Fe₃O₄ nanoparticles, with a 5 wt% concentration, applied to the Ti-6Al-4V alloy through electrophoretic deposition. The investigation examined various characteristics, including the morphology, surface roughness, thickness, electrochemical behavior, wettability, and biological properties such as bioactivity, cell adhesion, and cytotoxicity of the samples. Scanning electron microscopy (SEM) analysis revealed that the average size of the bioactive glass particles was 3.06 ± 1.64 µm, which is suitable for the electrophoretic deposition process. The findings show that the addition of iron oxide nanoparticles improves the corrosion resistance of the substrate. To assess bioactivity, the samples were immersed in simulated body fluid (SBF) for 7, 14, and 28 days. SEM images and elemental distribution maps showed the presence of calcium and phosphorus on the surface, which is indicative of bioactive behavior. Moreover, the sample containing Fe₃O₄ nanoparticles exhibited significant increases in surface roughness and hydrophilicity, which enhanced cell adhesion. Interestingly, cell viability decreased within 3 days for the composite sample of bioactive glass with 5 wt% Fe₃O₄ nanoparticles, whereas the sample coated with bioactive glass alone (without iron oxide nanoparticles) showed favorable cell viability.